Transparency in persuasive technology, immersive technology, and online marketing: Facilitating users' informed decision making and practical implications. (February 2023) - Wang, Ruijie; Bush-Evans, Reece; Arden-Close, Emily; Bolat, Elvira; McAlaney, John; Hodge, Sarah; Thomas, Sarah; Phalp, Keith
Abstract: In the current age of emerging technologies and big data, transparency has become an important issue for technology users and online consumers. However, there is a lack of consensus on what constitutes transparency across domains of research, not to mention transparency guidelines for designers and marketers. In this review, we explored the question of what transparency means in current research and practices by reviewing the literature in three domains: persuasive technology, immersive technology and online marketing. Literature reviewed, including both empirical research and position articles, covered multidisciplinary areas including computer science and information technology, psychology, healthcare, human computer interaction, business and management, law and public health. In this paper, we summarized our findings through a framework of transparency and provided insights into the different aspects of transparency, categorized into ten themes (i.e., Organizational Transparency, Information Transparency, Transparency of System Design, Data Privacy and Informed Consent, Transparency of Online Advertising, Potential Risks, User Autonomy, Informed Decision Making, Information Visualization, Personalization and User-centered design) along three dimensions (i.e., Types of transparency, Impact on User and Potential Solutions). Addressing aspects of transparency will facilitate users' autonomy and contribute to their informed decision making. Highlights: Transparency in persuasive technology, immersive technology, and online marketing involves a wide range of aspects. Lack of transparency exposes users to risks of technology and impacts users' autonomy and informed decision making. Potential solutions to improving transparency involve information visualization and a human-centered, personalized approach. Research across domains such as linguistics, eye-tracking and neuroscience is needed to improve online information design. Future research should consider social, economic, cultural, and environmental factors to achieve an adequate trade-off.